1998
DOI: 10.1172/jci448
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen toxicity and iron accumulation in the lungs of mice lacking heme oxygenase-2.

Abstract: Heme oxygenase (HO) activity leads to accumulation of the antioxidant bilirubin, and degradation of the prooxidant heme. Moderate overexpression of the inducible form, HO-1, is associated with protection against oxidative injury. However, the role of HO-2 in oxidative stress has not been explored. We evaluated survival, indices of oxidative injury, and lung and HO expression in HO-2 null mutant mice exposed to > 95% O2 compared with wild-type controls. Similar basal levels of major lung antioxidants were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(126 citation statements)
references
References 52 publications
(47 reference statements)
3
121
1
1
Order By: Relevance
“…Nath et al (2,41,42) showed that a decrease in HO activity predisposed rats to marked tubular interstitial inflammation and mortality after repetitive dosing with hemoglobin. It is also in agreement with those who have studied HO-2 deficiency in the heart and lung (43). A lowered HO activity in HO-2 (Ϫ/Ϫ) compared with HO-2 (ϩ/ϩ) mice therefore would diminish ferritin synthesis and increase tissue iron deposits.…”
Section: Discussionsupporting
confidence: 92%
“…Nath et al (2,41,42) showed that a decrease in HO activity predisposed rats to marked tubular interstitial inflammation and mortality after repetitive dosing with hemoglobin. It is also in agreement with those who have studied HO-2 deficiency in the heart and lung (43). A lowered HO activity in HO-2 (Ϫ/Ϫ) compared with HO-2 (ϩ/ϩ) mice therefore would diminish ferritin synthesis and increase tissue iron deposits.…”
Section: Discussionsupporting
confidence: 92%
“…31,49 These include heme oxygenase, 49,50 which recently has been shown to offer protection from the development of atherosclerosis and to reduce oxidation products in HDL. 51,52 Alternatively, the protective effect of HBO treatment may be mediated by the suppression of specific enzymes responsible for lipid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…If iron transport and storage proteins do not rapidly and effectively remove this LMrFe, the argument for HO as an antioxidant becomes flawed. Experiments with HO-2 knock-out mice reveal the accumulation of iron in the lung after hyperoxic exposure ; this occurs without the induction of ferritin [24]. Indeed, the protective effects attributed to HO might actually reside in the induction of ferritin, rather than in HO-1 itself, as was seen in a rodent rhabdomyolysis model [12].…”
Section: Figure 5 Hne Formationmentioning
confidence: 97%
“…There is much debate at present concerning the pro-oxidant or antioxidant nature of HO in various settings [2,[24][25][26]. Haem has pro-oxidant properties, so its removal by HO can be considered an important antioxidant effect [45].…”
Section: Figure 5 Hne Formationmentioning
confidence: 99%
See 1 more Smart Citation